FOREIGN EXPERIENCES IN DEVELOPING THE ECOLOGICAL AND AESTHETIC CONSCIOUSNESS OF YOUTH - Tursunov Abdimumin Shakhanovich (Scholar Express Journal, 2024)
In the article, the work carried out on the development of ecological and aesthetic consciousness of young people in today’s developed countries, the attitude of young people to nature and the environment, the methods and means of their education are disclosed. Also, in the research, the question of formation of ecological consciousness and aesthetic attitude towards nature of young people in developed countries was analyzed.
Keywords: Ecological-aesthetic consciousness; environment; nature